THE EFFECTIVENESS OF USING THE PHONETIC METHOD TO IMPROVE THE SPEAKING SKILLS OF STUDENTS IN SCHOOL AL-IRSYAD BULAAN KAMBA AGAM - Nadia Okta Nelsi; Fajriyani Arsya (TARBIYATUL ILMU: JURNAL KAJIAN PENDIDIKAN, 2025)
The problems of this research are that the students consider the Arabic language subject to be difficult to understand, the teacher’s lack of creativity in enhancing the students’ speaking skill, the results of the speaking skill test for primary school students, the students feel that the process of teaching speaking skill is less attractive, and the teacher did not use the phonetic method. In teaching the Arabic language. This research aims to find out the use of the phonetic method to improve the speaking skill of eighth grade students, and to find out the effectiveness of using the phonetic method to improve the speaking skill of eighth grade students. Based on the completion of the post-test in the experimental class and the control class in understanding vocabulary for seventh-semester students at the Bollan Campa Guidance Institute, the author found that in the experimental class in which the vocabulary card method with pictures was applied the average result of the pre-test was 52.09 and the post-test was 79.51 and in the control class in which Applying the method was repeated posttest with an average result of the pretest 61.40 and the posttest 68.43.